Digital Capability and Business Agility among Micro Enterprises - Zulhaziq Zulkifli,; Ahmad, Nurazwa; Tengku Nur Azila Raja Mamat, (Research in Management of Technology and Business, 2024)
The nationwide COVID-19 pandemic has caused several countries to use travel restrictions and movement controls. In Malaysia, the small business sector is one of the sectors most affected by the implementation of the Movement Control Order (MCO). Therefore, the use of digital views is increasingly important in helping to live a technological life in the new norm. The objective of this study is to identify the level of business agility, digital capability and the relationship between digital capability and the business agility among micro enterprises in Muar, Johor. To achieve the objective of the study, the researcher used a quantitative method, where the questionnaire was disclosed online using Google Form. A convenience sampling method was employed with a final of 361 responses among micro farmers. The Statistical Package for Social Sciences (SPSS) was used to conduct descriptive analyses, normality tests, Spearman's correlation and simple linear regression analysis. Descriptive results showed a high value of mean score for both variables. Furthermore, the findings of Spearman correlation is r=0.508 (p